TREND IN MORTALITY OF ELDERLY BY LAND TRANSPORT ACCIDENTS IN BRAZIL - Giovana Aparecida de Souza Scolari; Flávia Maria Derhun; Diogo Francisco Rossoni; Thais Aidar de Freitas Mathias; Carlos Alexandre Molena Fernandes; Lígia Carreira (Universidade Federal do Paraná, 2017)
The present study aimed to analyze the trend in mortality by land transport accidents among Brazilian elderly individuals, from 1996 to 2013. Ecological, time-series study with secondary data collected by the Mortality Information System in April, 2015 concerning deaths by transport accidents. There were 88,273 deaths of elderly individuals caused by land transport accidents in Brazil, in the study period. All Brazilian regions showed a rising trend in mortality by transport accidents, which were more significant in the Northeastern region, followed by the Southern, Northern, Southeastern and Central-Western regions. These findings reveal the importance of surveillance of transport accidents, to support the implementation of effective health promotion policies, prevention and reduction of these events.DESCRIPTORS: